A systematic review on community-based interventions for elder abuse and neglect. Issue 2 (27th May 2017) - Fearing, Gwendolyn; Sheppard, Christine L.; McDonald, Lynn; Beaulieu, Marie; Hitzig, Sander L.
ABSTRACT: Elder abuse and neglect is a societal issue that requires prevention and intervention strategies at the practice and policy level. A systematic review on the efficacy of community-based elder abuse interventions was undertaken to advance the state of knowledge in the field. The peer-reviewed literature between 2009 and December 2015 were searched across four databases. Two raters independently reviewed all articles, assessed their methodological quality, and used a modified Sackett Scale to assign levels of evidence. Four thousand nine hundred and five articles were identified; nine were selected for inclusion. Although there was Level-1 evidence for psychological interventions ( n = 2), only one study on strategies for relatives (START) led to a reported decrease in elder abuse. There was Level-4 evidence for conservatorship, an elder abuse intervention/prevention program (ECARE), and a multidisciplinary intervention ( n = 4), in which one study yielded significant decreases in elder abuse and/or neglect. The remaining three were classified as Level-5 evidence ( n = 3) for elder mediation and multidisciplinary interventions. There are limited studies with high levels of evidence for interventions that decrease elder abuse and neglect. The scarcity of community-based interventions for older adults and caregivers highlights the need for further work to elevate the quality of studies.